A Secure Protocol for Smart Meters using IoT Enabled Distribution Networks and Blockchain Security Mechanism - S, Madhura; L, Thilak Raj (Journal of Ubiquitous Computing and Communication Technologies, 2020)
Smart Cities, Homes and Communities are the spaces where IoT sensors are used to the fullest in the Utilities sector. Advanced Metering Infrastructure (AMI) providing the peer-to-peer communication between metering equipment that reads, calculate and provides the information related to distribution and measure the consumption. This paper outlines the network monitoring and management architecture that can be used in Smart Cities, homes and communities using the integrated IoT and Blockchain technology. Blockchain technology provides trustworthy resource monitoring of utilities for all members of the smart community that in-turn benefit the members of smart communities with enhanced monitoring and optimize the consumption of resources in protected and transparent way.